Sexual progressives : reimagining intimacy in Scotland, 1880-1914 - Cheadle, Tanya (Gender in history., 2020)
Sexual Progressives is a major new study of the feminists and socialists who campaigned against the moral conservatism of Victorian Scotland. Drawing on a range of sources, from letters and diaries to radical newspapers and utopian novels, its arguments disrupt current understandings of progressive thought and behaviour in fin de siecle Britain.